ROLE OF TOBACCO COMPANIES DISTORTED - SEIDENSTICKER,RB (Tufts Archival Research Center, 2007)
Letter to the editor of the Morning Herald from Liggett Group Inc. regarding the group Californians for Common Sense, a California group formed to oppose Proposition 5. Argues that the proposition was defeated because people did not want government regulations to substitute for their individual choice, not, as supporters claim, because it had access to the unlimited funds of the tobacco industry.